Participation in Public Expenditure Systems - Wagle, Swarnim (World Bank, Washington, DC, 2012)
This note makes an in-depth analysis of public expenditure budget management, and its necessary reforms. The note presents a number of successful cases from around the globe where a framework for participatory public expenditure system is presented, and where civic groups influenced stages budgets processes in a cyclic and interactive manner. Civic input can influence both the internal reform measures of the evaluated government agencies, as well as external evaluators, such as the report to the Auditor General in the parliament. Reforms to public expenditure systems have been given a high priority, as part of the Bank's lending instruments, focusing on making the public expenditure systems more transparent, accountable, and efficient toward the end of poverty reduction.